Spiritual Intelligence Among Santri - Kartika, Insan Sukma; Susanti, Raini Diah; Fitri, Siti Ulfah Rifa'atul (GLOBAL HEALTH SCIENCE GROUP, 2024)
An islamic boarding school is a place for shaping the character of adolescents. Students who study in an islamic boarding school are called santri. However, in reality, students still experience various socio-spiritual problems. This study aims to identify the level of spiritual intelligence in adolescent students at the Baiturrahman Islamic Boarding School in Bandung Regency. The quantitative method was used with a total sampling of 118 respondents, who were adolescent students at the Baiturrahman Islamic Boarding School in Bandung Regency at the Senior High School (SMA) level. The Spiritual Intelligence Self-Report Inventory (SISRI-24) scale was used. The validity of The Spiritual Intelligence Self-Report Inventory (SISRI-24) scale was found to have a product moment correlation coefficient greater than 0.388. Additionally, the reliability of the scale was tested using cronbach's alpha, and the resulting value was 0.789. Data analysis using univariate analysis. The results showed that the level of spiritual intelligence was in the high category (58.5%). The dimensions of Personal Meaning Production (PMP), Conscious State Expansion (CSE), and Transcendental Awareness (TA) are classified in the high spiritual intelligence category with percentages of 73.7%, 56.8%, and 55.9% respectively. The Critical Existential Thinking (CET) dimension, on the other hand, is at a moderate level with a percentage of 51.7%. Various efforts that can be made to improve CET can be through resilience training, a sense of honesty, and altruism, which often contributes to the ability to think and find purpose in life, thereby forming spiritual well-being.